Dominance of 2 Minute Oscillations near the Alfvén Surface - Zesen Huang; Marco Velli; Chen Shi; Yingjie Zhu; B. D. G. Chandran; Trevor Bowen; Victor Réville; Jia Huang; Chuanpeng Hou; Nikos Sioulas; Mingzhe Liu; Marc Pulupa; et al. (The Astrophysical Journal Letters)
Alfvén waves, considered one of the primary candidates for heating and accelerating the fast solar wind, are ubiquitous in spacecraft observations, yet their origin remains elusive. In this study, we analyze data from the first 19 encounters of the Parker Solar Probe and report the dominance of 2 minute oscillations near the Alfvén surface. The frequency-rectified trace magnetic power spectral density (PSD) of these oscillations indicates that the fluctuation energy is concentrated around 2 minutes for the “youngest” solar wind. Further analysis using wavelet spectrograms reveals that these oscillations primarily consist of outward-propagating, spherically polarized Alfvén wave bursts. Through Doppler analysis, we show that the wave frequency observed in the spacecraft frame can be mapped directly to the launch frequency at the base of the corona, where previous studies have identified a distinct peak around 2 minutes (~8 mHz) in the spectrum of swaying motions of coronal structures observed by the Solar Dynamics Observatory Atmospheric Imaging Assembly. These findings strongly suggest that the Alfvén waves originate from the solar atmosphere. Furthermore, statistical analysis of the PSD deformation beyond the Alfvén surface supports the idea of dynamic formation of the otherwise absent 1/ f range in the solar wind turbulence spectrum.